Kindlin-2 in pancreatic stellate cells promotes the progression of pancreatic cancer. (1st April 2017) - Yoshida, Naoki; Masamune, Atsushi; Hamada, Shin; Kikuta, Kazuhiro; Takikawa, Tetsuya; Motoi, Fuyuhiko; Unno, Michiaki; Shimosegawa, Tooru
Abstract: Pancreatic stellate cells (PSCs) play a pivotal role in pancreatic fibrosis associated with pancreatic ductal adenocarcinoma (PDAC). Kindlin-2 is a focal adhesion protein that regulates the activation of integrins. This study aimed to clarify the role of kindlin-2 in PSCs in pancreatic cancer. Kindlin-2 expression in 79 resected pancreatic cancer tissues was examined by immunohistochemical staining. Kindlin-2-knockdown immortalized human PSCs were established using small interfering RNA. Pancreatic cancer cells were treated with conditioned media of PSCs, and the cell proliferation and migration were examined. SUIT-2 pancreatic cancer cells were subcutaneously injected into nude mice alone or with PSCs and the size of the tumors was monitored. Kindlin-2 expression was observed in PDAC and the peritumoral stroma. Stromal kindlin-2 expression was associated with shorter recurrence-free survival time after R0 resection. Knockdown of kindlin-2 resulted in decreased proliferation, migration, and cytokine expression in PSCs. The PSC-induced proliferation and migration of pancreatic cancer cells were suppressed by kindlin-2 knockdown in PSCs. In vivo, co-injection of PSCs increased the size of the tumors, but this effect was abolished by kindlin-2 knockdown in PSCs. In conclusion, kindlin-2 in PSCs promoted the progression of pancreatic cancer. Highlights: Stromal kindlin-2 expression was associated with shorter recurrence-free survival time after R0 resection. Knockdown of kindlin-2 decreased proliferation, migration, and IL-6 expression in pancreatic stellate cells (PSCs). PSC-induced proliferation and migration of pancreatic cancer cells were suppressed by kindlin-2 knockdown in PSCs. Co-injection of PSCs with SUIT-2 cells increased tumorigenicity, which was abolished by kindlin-2 knockdown in PSCs. Collectively, our results suggest a novel tumor-promoting role of kindlin-2 in PSCs.